WHEN TRAUMA CANNOT SPEAK: SILENCE AND DESTRUCTIVE PLASTICITY IN HAN KANG’S THE VEGETARIAN - Sysilia Putri Agustin; Kholidah Uci Elly; Ningtyas Sulistya (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2026)
Structural violence and patriarchal domination remain significant threats to women’s existence, particularly within collective societies. This study examines Han Kang’s novel, The Vegetarian, to investigate the protagonist’s radical transformation as a response to systemic oppression. While existing research often focuses on psychological or feminist perspectives, there is a lack of analysis regarding how structural violence materially produces a new subjectivity through Catherine Malabou’s theory of destructive plasticity. This qualitative study employs a thematic approach to analyze the novel, complemented by a biographical approach to trace the author's life trajectory through secondary data, specifically published written interviews with Han Kang spanning from 2016 to 2024. The analysis suggests that Yeong-hye’s transformation constitutes an "ontological accident" triggered by latent childhood trauma and domestic objectification. This process produces a "New Wounded" subject who adopts a vegetal identity to achieve total detachment from a world perceived as inherently violent. Furthermore, the study posits that the erasure of Yeong-hye’s voice reflects South Korea's socio-legal and patriarchal structures, representing a strategic choice to highlight the subject’s alienation. Ultimately, this research concludes that becoming non-human constitutes a radical political act of extraction, allowing the subject to exist beyond the reach of patriarchal jurisdiction.